2017
DOI: 10.4103/ija.ija_22_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and cost-effectiveness of 0.55% ortho-phthalaldehyde and 2% glutaraldehyde for disinfection of laryngoscopes: A prospective pilot study

Abstract: Background and Aims:The laryngoscope is a potential source of cross-infection as it involves contact with the mucous membrane, saliva and occasionally blood. This study compared efficacy and cost-effectiveness of two Centre for Disease Control approved agents for disinfection of laryngoscope blades.Methods:One hundred and sixty patients requiring laryngoscopy and intubation for general anaesthesia were randomly allocated into two groups. After tracheal intubation, used laryngoscope blades were cleaned with tap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…Most of the studies (n = 4) were published in 2017, with one study each published in 2013, 2016, and 2018 . One study was conducted in the United States and two in India . One study each was conducted in Brazil, Iran, Korea, and the United Kingdom .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the studies (n = 4) were published in 2017, with one study each published in 2013, 2016, and 2018 . One study was conducted in the United States and two in India . One study each was conducted in Brazil, Iran, Korea, and the United Kingdom .…”
Section: Resultsmentioning
confidence: 99%
“…The researchers concluded that 2% glutaraldehyde and 0.55% OPA are equally effective for processing laryngoscope blades; however, processing with 0.55% OPA requires a shorter processing time. Because there was microbial growth on 2.5% of the laryngoscope handles after disinfection with 0.5% chlorhexidine germicidal wipes, the researchers also concluded the wipes were not effective for disinfection of laryngoscope handles …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations